2019
DOI: 10.1111/jgs.16089
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Is Associated With Mortality in Adults Aged 80 Years and Older: A Prospective Study

Abstract: OBJECTIVES Diet quality has been associated with health outcomes and quality of life. However, the association between diet quality and mortality in older people, those aged 80 years and older, is understudied. Therefore, we conducted a prospective study to examine whether better diet quality, assessed by a validated dietary screening tool (DST), was associated with lower mortality in those aged 80 years and older. METHODS Our study included 1990 participants (812 men and 1178 women), with a mean age of 84.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
(73 reference statements)
0
18
1
Order By: Relevance
“…Social and environmental factors were found as determinants of eating behavior in a previous study (56). Therefore, nutrition support programs are important for vulnerable people to improve their dietary intake behavior (57,58), especially during the pandemic and home confinement (30,31). Our study shows that people who were under the lockdown period had a higher likelihood of depression.…”
Section: Discussionmentioning
confidence: 47%
“…Social and environmental factors were found as determinants of eating behavior in a previous study (56). Therefore, nutrition support programs are important for vulnerable people to improve their dietary intake behavior (57,58), especially during the pandemic and home confinement (30,31). Our study shows that people who were under the lockdown period had a higher likelihood of depression.…”
Section: Discussionmentioning
confidence: 47%
“…After dual screening, 11 547 relevant studies were identified. The body of evidence included 153 articles (involving 6 550 664 individuals), of which 1 was from a randomized clinical trial (RCT) 18 and 152 were from observational studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
“…Studies enrolled adults and older adults (aged 17-84 years at baseline) from 28 countries with a high or very high Human Development Index 16 classification (Australia, Belgium, Canada, Czech Republic, Croatia, Denmark, Finland, France, Germany, Greece, Hong Kong, Hungary, Iran, Italy, Japan, Korea, Norway, Netherlands, Poland, Portugal, Russia, Serbia, Singapore, Spain, Sweden, Switzerland, United Kingdom, and United States). Fifty-three studies 21 , 23 , 24 , 27 , 29 , 32 , 33 , 37 , 39 , 40 , 42 , 43 , 44 , 46 , 47 , 52 , 56 , 57 , 58 , 59 , 60 , 61 , 72 , 73 , 74 , 78 , 83 , 86 , 94 , 95 , 96 , 98 , 100 , 101 , 102 , 104 , 107 , 110 , 118 , 125 , 126 , 127 , 129 , 135 , 137 , 150 , 158 , 160 , 161 , 163 , 166 originated from the US. Some studies exclusively enrolled female 29 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations